The Rho GTPase Cell Division Cycle 42 Regulates Stereocilia Development in Cochlear Hair Cells - Du, Haibo; Zhou, Hao; Sun, Yixiao; Zhai, Xiaoyan; Chen, Zhengjun; Wang, Yanfei; Xu, Zhigang (Frontiers in Cell and Developmental Biology, 2021)
Stereocilia are actin-based cell protrusions on the apical surface of inner ear hair cells, playing a pivotal role in hearing and balancing sensation. The development and maintenance of stereocilia is tightly regulated and deficits in this process usually lead to hearing or balancing disorders. The Rho GTPase cell division cycle 42 (CDC42) is a key regulator of the actin cytoskeleton. It has been reported to localize in the hair cell stereocilia and play important roles in stereocilia maintenance. In the present work, we utilized hair cell-specific Cdc42 knockout mice and CDC42 inhibitor ML141 to explore the role of CDC42 in stereocilia development. Our data show that stereocilia height and width as well as stereocilia resorption are affected in Cdc42-deficient cochlear hair cells when examined at postnatal day 8 (P8). Moreover, ML141 treatment leads to planar cell polarity (PCP) deficits in neonatal hair cells. We also show that overexpression of a constitutively active mutant CDC42 in cochlear hair cells leads to enhanced stereocilia developmental deficits. In conclusion, the present data suggest that CDC42 plays a pivotal role in regulating hair cell stereocilia development.